Perceived Stress, Psychological Flexibility Profiles, and Mental Health During COVID-19: A Latent Profile Analysis - Deng Y; Huang P; Yang Q; Ye B (Psychology Research and Behavior Management, 2023)
Yuhong Deng,1 Pengfei Huang,1 Qiang Yang,2 Baojuan Ye1 1School of Psychology, School of Education, Center of Mental Health Education and Research, Jiangxi Normal University, Nanchang, People’s Republic of China; 2School of Education, Jiangxi Normal University, Nanchang, People’s Republic of ChinaCorrespondence: Baojuan Ye, School of Psychology, School of Education, Center of Mental Health Education and Research, Jiangxi Normal University, Nanchang, People’s Republic of China, Email yebaojuan0806@163.comPurpose: Although the link between psychological flexibility and healthy functioning has been widely analyzed, the employed measurements often lacked accuracy. The current study introduced a person-centered approach that identified subgroups of college students across the dimensions of the Personalized Psychological Flexibility Index (PPFI) and explored how these subgroups relate to a risk factor (perceived stress) and mental health outcomes (depression, anxiety, negative affect, and positive affect) in the context of COVID-19.Methods: A sample of 659 participants (Mage = 19. 99, SD = 1.27; 57.97% females) completed the questionnaires online. Latent profile analysis (LPA) was employed to determine the optimal number of subgroups or profiles. Then, multinomial logistic regression and analyses of variance were used to identify variables associated with profile membership.Results: LPA identified three distinct profiles (active strategy, inconsistent strategy, and passive strategy). Furthermore, multinomial logistic regressions indicated that students with high perceived stress were more likely to be in the passive strategy group than the active strategy group (β = − 0.104, OR = 0.901, p < 0.001) and the inconsistent strategy group (β = − 0.087, OR = 0.917, p < 0.001). Additionally, analyses of variance revealed that the three profiles differed in depression (η2 = 0.062, p < 0.001), anxiety (η2 = 0.059, p < 0.001), negative affect (η2 = 0.047, p < 0.001), and positive affect (η2 = 0.048, p < 0.001).Conclusion: The current study employed LPA based on the PPFI to identify and confirm three profiles of psychological flexibility. We found that perceived stress and mental health outcomes were associated with these three profiles. This study offers a new perspective on understanding psychological flexibility through a person-centered approach. Furthermore, interventions aimed at reducing college students’ perceived stress during the COVID-19 crisis are critical for preventing the deterioration of psychological flexibility.Keywords: SARS-CoV-2, Personalized Psychological Flexibility Index, stress, mental well-being, latent profile analysis